(untitled) (Research, Society and Development, 2023)
Defined as a hypertensive emergency (HE) characterized by a marked and acute increase in blood pressure, specifically diastolic pressure, being greater than 120 mmHg, associated with signs of target-organ damage. These may include pulmonary edema, cardiac ischemia, neurological deficits, acute renal failure, aortic dissection, and eclampsia. Given the epidemiological importance of HE, this article aims to discuss the pathophysiological mechanisms of the disease. This study is a narrative review with the purpose of discussing and describing HE and its pathophysiology, as well as demonstrating how this disease affects the personal lives of affected individuals. The following databases were used: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine), with scientific data from March 9, 2023, with no language restriction and no restriction on the year of publication. Several studies show the pathophysiology of HE, which includes conditions associated with increased intravascular volume, peripheral vascular resistance, and also the possibility of reduced production of endogenous vasodilators that can lead to greater vasoreactivity that is capable of generating emergence. In short, sepsis remains a significant burden on healthcare systems around the world.